Penerapan Pembelajaran Kontekstual “Syukur dalam Aksi” untuk Meningkatkan Sikap Syukur Siswa Kelas V SD Islam Excellent Plus Bukittinggi - Darmansyah AS (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
This study aims to examine the effectiveness of the contextual learning model "Gratitude in Action" in enhancing the gratitude attitude of fifth-grade students at SD Islam Excellent Plus Bukittinggi. The research was motivated by observations indicating that students' gratitude practices were limited to formal rituals without deeper internalization. A quasi-experimental method with a single-group pretest-posttest design was employed, involving 32 students. Quantitative data were collected through pre- and post-intervention surveys, while qualitative data were derived from teacher observations, student journals, and interviews. The results showed a statistically significant increase in students' gratitude scores (from 2.4 to 3.5 on a 4-point scale, p < 0.05). Behavioral observations revealed improved spontaneous expressions of gratitude, increased peer collaboration, and proactive acts of kindness. The model’s four stages—contextualization, experience, reflection, and transfer—proved effective in linking gratitude concepts to real-life actions. The study concludes that contextual learning grounded in Islamic values strengthens gratitude attitudes holistically. Recommendations include expanding teacher training, integrating family involvement, and replicating the model in other Islamic elementary schools with adjustments for local contexts.